Perencanaan Komunikasi Berbasis Internet pada Kementerian Agama Provinsi Jawa Tengah - Naiza Rosalia; Mutia Rahmi Pratiwi (UPT Publikasi Ilmiah Unisba, 2022)
Abstract. The Ministry of Religion of Central Java Province has programs to reduce divorce rates, including BINWIN and KUA Kick Off in the BP4 division. However, communication activities for these programs have not been carried out massively. In line with this, the divorce rate is still increasing, it is known that it is no longer an economic problem that supports this, but a lack of mutual trust in married couples. This study aims to prepare a communication planning document for Public Relations of the Ministry of Religion for activities to communicate existing programs. The case study method with data collection techniques through interviews, documentation, and observations was carried out to obtain comprehensive data. The result of the research is the design of a communication planning document by determining the key message